Does the "no" to death offer the "yes" to therapeutic obstination? - Karla Cristiane Oliveira Silva; Elisabeta Albertina Nietsche; Stefanie Griebeler Oliveira; Alberto Manuel Quintana; Silomar Ilha (Universidade Federal de Santa Maria, 2012)
Objective: this article aims at discussing the denial of death and the therapeutic obstination practice. Methods: two reflexive categories were developed. The first one was the culture of denial of death, and the second one was the technology to "put death away". Results: in the first category, psycho-socio-cultural aspects were described, approaching the meanings of the human finitude, and possible actions that could occult the end of life from the routine of people. The second one concerns definitions of therapeutic obstination, bioethical questions that approach such matter, and professional and family interventions for the development of such practice. Conclusion: the "no" to death may favor therapeutic obstination, and, while the culture of denying death and the abusive use of technology regarding extending life remain, the challenge to pursue more humanitarian actions considering health practices will be even greater